Woman's Identity Crisis in the Clash of Cultures: A Study of Betool Khedairi's Novel: A Sky So close - جبار هاشم الزبيدي شيماء هادي عبد الرضا (College of Education for Women, 2019)
This paper is an attempt to clarify the impact of Postcolonialism, one of the most challenging fields of study that has emerged in recent years, on representations of women in once-colonised countries and in Western locations. It discusses the influence of cultural differences on the status and identity of a woman who experience _multiculturalism'. The study is an analytical reading of a contemporary novel written by the Iraqi writer Betool Al- Kudairi. The emphasis lies on the clash between two different cultures and traditions represented by the British mother and the Iraqi father and its effect on the life and identity of the protagonist. The main focus is on idea of _hybrid identity' and the absence of the sense of belonging. A Sky so Close is a close look into the clash between East and West and into the soul of a woman formed by two cultures yet fully accepted by neither.